Analysis of The Influence of Attitude Toward Digital Products and Perception of Technology Benefits on Intention to Purchase Digital Products - Syaid Agustiar, Muhammad; Widia Nurdiani, Tanti; Hawari, Yusmita; Lubis, Zurlina; Lubis, Andriani (SEULANGA SYSTEM PUBLISHER, 2024)
This study examines how attitudes toward smartwatches and their consequences for behavioral intention to use are influenced by perceived utility, perceived ease of use, and subcultural appeal. Researchers will employ a descriptive research design type of study. Questionnaires were distributed to collect data using convenience and non-probability sampling. This study's population consists of smartwatch wearers. In this study, convenience sampling is combined with a non-probability sampling strategy. The structural equation model method will be used to examine the data in this study. Several conclusions were drawn from this study's data processing and analysis results. First, their mobility positively impacts the perceived ease of use of smartwatches. Perceived usefulness is positively affected by perceived simplicity of usage. Third, attitudes regarding smartwatches are positively impacted by perceived utility. Fourth, perceptions regarding smartwatches are positively affected by subcultural appeal. Fifth, behavioral intention to use is positively impacted by perceived usefulness, meaning that consumers are more likely to continue using a smartwatch if they believe it to be beneficial. Lastly, a user's attitude about their wristwatch positively impacts their behavioral intention to use it. This means that the more positively a user feels about their smartwatch, the more likely they will use it going forward.